N-(3-(tert-Butyl)-1-methyl-1H-pyrazol-5-yl)-4-methyl-N-tosylbenzenesulfonamide - Diana Becerra; Juan-Carlos Castillo (Molbank)
N-(3-(tert-Butyl)-1-methyl-1H-pyrazol-5-yl)-4-methyl-N-tosylbenzenesulfonamide was efficiently synthesized in good yield through a triethylamine-mediated sulfonamidation reaction of 3-(tert-butyl)-1-methyl-1H-pyrazol-5-amine with 4-methylbenzenesulfonyl chloride in acetonitrile at room temperature. The pyrazole-based benzenesulfonamide was fully characterized using FT-IR, NMR, and HMRS techniques.